2009
DOI: 10.4197/med.16-4.2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Feeding Habits in a Sample of Preschool Children in Severe Early Childhood Caries (S-ECC)

Abstract: The aim of the present study is to investigate dietary and feeding habits in a sample of preschool children with Severe Early Childhood Caries. The design followed a case control study; sixty children were selected, and another thirty caries free children were selected as controls. Children were healthy, diagnosed as Severe Early Childhood Caries, with age range 36-71 months. A clinical examination was done to measure decayed, missing and filled index. A questionnaire interview was performed to evaluate dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 49 publications
(60 reference statements)
4
28
0
Order By: Relevance
“…Inappropriate use of bottle-feeding among children plays a central role in the etiology and severity of ECC. A number of studies had found significant correlations between ECC and prolonged bedtime use of bottles with sweetened content [11,12]. In the current study, it has been demonstrated that prolonged duration and high frequency of bottle-feeding may indeed induce the ECC occurrence.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Inappropriate use of bottle-feeding among children plays a central role in the etiology and severity of ECC. A number of studies had found significant correlations between ECC and prolonged bedtime use of bottles with sweetened content [11,12]. In the current study, it has been demonstrated that prolonged duration and high frequency of bottle-feeding may indeed induce the ECC occurrence.…”
Section: Discussionsupporting
confidence: 62%
“…Studies from India had found that children who sleep with nursing bottles had a higher risk to get dental caries [11]. Likewise, a study conducted in Jeddah (Saudi Arabia) showed that children who bottle-fed in bed had 9% higher risk to get caries compared to children who did not [12]. Similar findings in South-West Germany indicated a significant correlation between the usage of nursing bottles in bed and severe ECC [13].…”
Section: Introductionmentioning
confidence: 79%
“…A total number of 7 articles were included in this systemic review. Three of them were case control studies [24,32,33] and four were cross sectional [8,9,34,35] . Their base populations were recruited from Riyadh [8,[32][33][34] , Jeddah [9,24] and Tabuk [35] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Wyne et al [34] specified that the two carious lesions have to be on the labial surface. A more specific definition was used by Almushayt et al [24] they defined Severe ECC according to the American Academy of Pediatric Dentistry (AAPD 2006-2007) [21] . They described Severe EEC as the presence of one or more decayed (non cavitated or cavitated lesions), missing tooth due to caries or filled tooth surfaces in any primary tooth in a child 71 month of age or younger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation